High-Dose-Rate Interstitial Brachytherapy for Deeply Situated Gynecologic Tumors Guided by Combination of Transrectal and Transabdominal Ultrasonography: A Technical Note - Shimizu, Yuri; Murakami, Naoya; Chiba, Takahito; Kaneda, Tomoya; Okamoto, Hiroyuki; Nakamura, Satoshi; Takahashi, Ayaka; Kashihara, Tairo; Takahashi, Kana; Inaba, Koji; Okuma, Kae; Nakayama, Yuko; et al. (Frontiers in Oncology, 2022)
Background and Purpose: High-dose-rate interstitial brachytherapy (HDR-ISBT) is recommended to obtain a better local tumor control for uterine cancer patients in situations such as bulky lesions or tumors with irregular shape. Our group uses real-time transrectal ultrasonography (TRUS) to guide freehand interstitial needle insertion. Occasionally, target tumors locate deeper beyond the rectum and cannot be visualized by TRUS. Computed tomography can guide needles to deeply located tumors, but in such cases, repeated image obtainment is required to achieve ideal needle localization. In this report, we present nine cases of patients who underwent HDR-ISBT for deeply situated tumors guided by a combination of transrectal and transabdominal ultrasonography (TR/TA-US). Material and Methods: Nine uterine cancer patients whose tumor located deeper than the reach of TRUS and underwent HDR-ISBT guided by TR/TA-US were presented. All nine cases had no distal organ metastasis and underwent external beam radiation therapy (EBRT) to the pelvic region for 45-50.4 Gy in 25-28 fractions followed by boost HDR-ISBT for deeply situated tumors guided by TR/TA-US. Results: There were seven cervical cancer and two endometrial cancer patients: six with extensive uterine corpus invasion, one cervical cancer with massive pelvic lymph node metastasis, one cervical cancer with postoperative pelvic recurrence, and one had ovarian metastasis. The median follow-up period was 15 months (range 3-28 months). The average clinical target volume at the time of first ISBT was 131 ml (range 44-335 ml). The linear distance from the vaginal entrance to the deepest part of the tumor at first time brachytherapy of nine cases was 14.0 (9.0 -17.0) cm. ISBT dose fractionation was 24-30 Gy in four or five fractions. Seven out of nine cases had no local recurrence in the follow-up period. One had local in-field recurrence 25 months after ISBT. Another case with carcinosarcoma could not obtain local control and underwent salvage hysterectomy for a residual uterine tumor eleven months after ISBT. Four cases had an extra-field recurrence in lymph nodes or distant organs. Conclusions: In brachytherapy for gynecologic malignancies, deeply situated tumors located out of reach of TRUS may obtain favorable local control by HDR-ISBT guided with TR/TA-US.